IMPROVING THE SATISFACTION OF INDONESIAN MIGRANT WORKERS IN OBTAINING POLICE RECORD CERTIFICATES - Supriyadi Supriyadi; Hardi Utomo; Ambar Istiyani (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the influence of the comfort of facilities and infrastructure, the ease of service procedures, and the behaviour of officers on the satisfaction of Indonesian Migrant Workers (PMIs) in obtaining a Police Record Certificate (SKCK) at the Administrative Services Section of the Directorate of Security Intelligence, Regional Police, Central Java. Previous studies have examined the level of community satisfaction in obtaining SKCKs from police institutions, but this study focuses specifically on PMIs, who may be more susceptible to marginalizing treatment and subpar public services. The quantitative research population consists of PMIs applying for SKCK, with a sample of 100 respondents. Data were analyzed using multiple linear regression, t-test, f-test, and coefficient of determination. The research results indicate that the comfort of facilities and infrastructure, the ease of service procedures, and the officers' behaviour all have a significant partial and simultaneous influence on PMI satisfaction. To improve PMI satisfaction in obtaining SKCKs, it is necessary to simplify the application process, develop and maintain the facilities and infrastructure, especially the parking area, and provide education and training to enhance the officers' professional competence.